Implication of Broken Family in Predicting Juvenile Delinquency Towards: Intervention Program: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Juvenile Delinquency is a prevalent issue in the community, with adults disappointed andafraid that children from broken families are not eligible to be imprisoned. PreventiveMeasures for Juvenile Delinquency aim to explain the relationship between broken Familiesand Juvenile Delinquency and promote action plans to prevent further damage. Economicdifficulties, such as poverty, can increase the risk of delinquency for children from brokenhomes. Since 2020, there has been an increase in youth violence nationwide. To help childrenfrom broken homes succeed, it is crucial that parents, educators, and policymakers addressthese problems and offer support and resources. Researchers agreed that family counselingand child assessments are crucial components in preventing broken families and juveniledelinquency, as well as conducting seminars and other forms of recreation.The findings showed that a moderate amount of data affirms the idea that a broken family isassociated with a higher risk of juvenile delinquency. It has also been observed thatinadequate parental supervision has a significant impact on juvenile delinquency, particularlywhen the parent exhibits excessive permissiveness and is unable to control the use ofsubstances like alcohol. This causes the child to feel neglected and emotionally deprived,which causes them to behave inappropriately outdoors and at school.Broken families and juvenile delinquency have been studied extensively, and research hasshown that children from broken families are at a higher risk of participating in delinquentconduct than those from intact homes. This association has been shown in people of allcultures, socioeconomic groups, and family structures and is due to the absence of parentalcontrol and direction. Children who experience this neglect may act out or engage in riskybehavior in an effort to gain attention.
Keywords: Criminology